Peptides extracted from edible mushroom: Lentinus squarrosulus induces apoptosis in human lung cancer cells - Arisara Prateep; Somruethai Sumkhemthong; Maneewan Suksomtip; Pithi Chanvorachote; Chatchai Chaotham (Taylor & Francis Group, 2017)
Context: Lentinus squarrosulus Mont. (Polyporaceae) is an interesting source of diverse bioactive compounds. Objective: This is the first study of the anticancer activity and underlying mechanism of peptides extracted from Lentinus squarrosuls. Materials and methods: Peptides were isolated from the aqueous extract of L. squarrosulus by employing solid ammonium sulphate precipitation. They were further purified by ion-exchange chromatography on diethylaminoethanol (DEAE)-cellulose and gel filtration chromatography on Sephadex G25. Anticancer activity was investigated in human lung cancer H460, H292 and H23 cells cultured with 0-40 μg/mL of peptide extracts for 24 h. Cell viability and mode of cell death were evaluated by MTT and nuclear staining assay, respectively. Western blotting was used to investigate the alteration of apoptosis-regulating proteins in lung cancer cells treated with peptide extracts (0-20 μg/mL) for 24 h. Results: The cytotoxicity of partially-purified peptide extracts from L. squarrosulus was indicated with IC50 of ∼26.84 ± 2.84, 2.80 ± 2.14 and 18.84 ± 0.30 μg/mL in lung cancer H460, H292 and H23 cells, respectively. The extracts at 20 μg/mL induced apoptosis through the reduction of anti-apoptotic Bcl-2 protein (∼0.5-fold reduction) and up-regulation of BAX (∼4.5-fold induction), a pro-apoptotic protein. Furthermore, L. squarrosulus peptide extracts (20 μg/mL) also decreased the cellular level of death receptor inhibitor c-FLIP (∼0.6-fold reduction). Conclusions and discussion: This study provides the novel anticancer activity and mechanism of L. squarrosulus peptide extracts, which encourage further investigation and development of the extracts for anticancer use.